Peningkatan Ketuntasan Hasil Belajar Matematika Menggunakan Model Cooperative Learning Tipe STAD melalui Pemanfaatan Alat Peraga - Bambang Winarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to improve the mastery learning of Grade XI students of SMK Negeri 3 using the cooperative learning model type STAD through the use of teaching aids. This study uses descriptive qualitative and quantitative approaches and this type of research is classroom action research. Data collection methods use observation, tests and documentation. The results obtained in this study are student learning outcomes. This shows that in teaching and learning activities with contextual learning students become very active. While the mastery learning of students classically in the first cycle reached 77.5%, increasing in the second cycle to 90% so that only a few students have not yet completed their studies. This shows that STAD type cooperative learning can be considered as a learning model used by teachers. Based on the results of data analysis and discussion, the implementation of STAD Cooperative learning can improve student learning outcomes, the application of these methods can attract the attention of students to participate in teaching and learning activities until the end of the lesson with a pleasant learning atmosphere so that it can lead to increased student learning outcomes. Conclusion, there is a significant increase in student mathematics learning outcomes using the cooperative learning model type STAD through the use of teaching aids. Keywords: Learning Outcomes, Cooperative Learning, TYPE STAD.